A Proverb Revival? On Current Proverb Use in the German-Speaking Part of Switzerland - Hrisztova-Gotthardt, Hrisztalina (Tautosakos darbai, 2026)
The paper’s main objective is to examine the current paremiological situation in the German-speaking part of Switzerland and to investigate to what extent proverbs are present in modern language use, the specific areas and contexts in which they play an essential role, and whether they are used more often in their original or modified forms. For this purpose, a corpus of examples illustrating the current use of traditional and modern proverbs, as well as their deliberate innovations, was analysed from both quantitative and qualitative perspectives. The examples were collected between 2019 and 2025 as part of a small field research project in the Swiss cantons of Basel City, Basel Country, Berne, and Solothurn. The analysis reveals that traditional and modern proverbs, along with their deliberate innovations, remain undoubtedly an essential part of contemporary language use and continue to play a significant role in various areas of life, including advertising, culture and tradition, political and civil discourse, and the public space in general. Within the domains of language use examined, proverbs occur far more often in their modified than in their original form.